2014
DOI: 10.1155/2014/953181
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Trace Elements in Hair of the Female Population with Different Types of Cancers in Wielkopolska Region of Poland

Abstract: Background. Cancer constitutes a major health problem worldwide. Thus, search for reliable and practical markers of the disease process remains the key issue of the diagnostic process. Objectives. The study aims at linking the trace element status of an organism, assessed by hair analysis, with the occurrence of cancer diseases. Material and Methods. Hair samples were collected from 299 patients with cancer diseases confirmed by a histopathological test and from 100 controls. Cancer patients were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Cancers: As in the case with ND, differential PTMs and expression of proteins are manifested in response to cancer. Also differential expression of various trace elements in hair have been found for different types of cancer, in a study carried out among Polish [63] and Indian [64] populations. X-ray diffraction of hair, used in combination with mammography has been reported to significantly improve the sensitivity and diagnostic accuracy for invasive Breast Cancer [65].…”
Section: Neurodegenerative Diseases (Nd)mentioning
confidence: 97%
“…Cancers: As in the case with ND, differential PTMs and expression of proteins are manifested in response to cancer. Also differential expression of various trace elements in hair have been found for different types of cancer, in a study carried out among Polish [63] and Indian [64] populations. X-ray diffraction of hair, used in combination with mammography has been reported to significantly improve the sensitivity and diagnostic accuracy for invasive Breast Cancer [65].…”
Section: Neurodegenerative Diseases (Nd)mentioning
confidence: 97%
“…In addition, the levels of compounds found in human hair reflect a medium-long exposure time since hair grows approximately 1 cm per month. Consequently, the concentration of an analyte in this matrix represents its level in the body medium from which it was formed, and provides information on "historical" intake from air, water, food, and dermal contact [16] of a great number of environmental contaminants, including organic compounds [17][18][19][20] and inorganic elements [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Trace element analysis is a common method for evaluating health state in living tissues ( 6 , 7 ). As most of exertion and also toxic materials which lead to disorders are accumulated in body tissues such as hair.…”
Section: Introductionmentioning
confidence: 99%
“…As most of exertion and also toxic materials which lead to disorders are accumulated in body tissues such as hair. It seems that measuring the concentrations of these elements can be a useful method for diagnosis of such disease ( 6 ). Many studies have reported that this type of analysis can be helpful for diagnosis of neoplasms and cancers ( 8 - 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation